2015
DOI: 10.1016/j.watres.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Direct contact membrane distillation for the concentration of saline dairy effluent

Abstract: The ability of direct contact membrane distillation to concentrate the waste effluent from salty whey, a by-product from the cheese making industry has been investigated. The effect of trace protein in the feed, cross-flow velocity and feed acidity were the factors examined. Flat Sheet PTFE membranes of nominal pore sizes 0.05, 0.22 and 0.45 μm were utilised. A decline in feed flux in the presence of trace protein in the feed was observed, but liquid penetration through the membrane could still be prevented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…However, due to wetting, this slight pressure caused a reverse liquid flow exceeding forward distillation flux. The standard hydrophobic PTFE membrane was, therefore, not suitable for MD processing of stick water, however, approaches are being considered by researchers to minimise wetting, such as pore size on other available membrane types [ 36 ], or more novel developed materials [ 37 ]. The focus in our work is to explore hydrophilic PU-coated hydrophobic PTFE (PU-PTFE) as a means to prevent wetting.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to wetting, this slight pressure caused a reverse liquid flow exceeding forward distillation flux. The standard hydrophobic PTFE membrane was, therefore, not suitable for MD processing of stick water, however, approaches are being considered by researchers to minimise wetting, such as pore size on other available membrane types [ 36 ], or more novel developed materials [ 37 ]. The focus in our work is to explore hydrophilic PU-coated hydrophobic PTFE (PU-PTFE) as a means to prevent wetting.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous efforts by scientists and engineers have improved the effectiveness of membrane-based processes for the removal of color and toxicity (Alcaina-Miranda et al, 2009;Aouni et al, 2012;Han et al, 2009;Mo et al, 2008). In particular, membrane distillation (MD), an emerging membrane-based technology, has generated interest because it can achieve a high rejection rate under mild temperatures and normal atmospheric pressure (Alkhudhiri et al, 2012;Kezia et al, 2015;Liao et al, 2014;. MD uses a hydrophobic porous membrane to separate the hot feed stream and the cold stream (Elimelech, 2014), whose temperature difference creates a trans-membrane vapor pressure difference that drives the vapors from the hot side to the cold side through the membrane pores (Hassan and Fath, 2013;Woo et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…According to the water vapor cooling-down method, the MD process can be classified into four different configurations [5]. By survey of the previous studies, it can be found that among these different MD processes, direct contact membrane distillation (DCMD) is the widely adopted configuration due to its simplicity and reasonably high water flux [32][33][34][35][36][37]. Therefore, in this study, DCMD configuration is used to evaluate the separation properties of the hydrophobic ceramic membranes prepared using the freeze drying tape casting method.…”
Section: Introductionmentioning
confidence: 99%